"Living More Through Knowing More": College Education in Prison Classrooms. Issue 4 (November 2020) - Kallman, Meghan Elizabeth
A growing national focus on prison reform has led to a resurgence of interest in carceral education. However, and although college education prison is different from college education in the community, relatively little scholarship has explored why or how these variations exist, what they mean, or how they have changed over time. The present paper aims to help fill this gap, exploring the significance of this context for adult learning. I ask: how does the context of a prison shape classroom dynamics and student learning? In answering the question, I employ qualitative and ethnographic methods that focus on giving voice to the perspective of the student-inmates themselves. I find that the isolated and oppressive characteristics of the prison can, paradoxically, offer unique opportunities for learning and scholarly achievement among incarcerated students. The paper's findings invite reflection about the types of educational strategies often employed in prisons, and provide baseline data on some important social dynamics within prison classrooms.